Radical Groin Dissection - Carriquiry, Luis A; Hernández, Walter; Borges, J Freddy; Mesa, Guillermo; Priario, Julio César (Cirugía del Uruguay, 1981)
Radical groin dissections performed in patients with melanoma and less frecuently with inferior limb epidermoid carcinoma, anal' carcinoma or soft tissue sarcomas are reviewed by the authors.